Barriers to family-centred care of hospitalised children at a hospital in Gauteng - Tsholofelo C. Malepe; Yolanda Havenga; Paulina D. Mabusela (AOSIS, 2022)
Background: Hospitalisation is a stressful event for the admitted child and the family. The unfamiliar and stressful hospital environment could increase children's anxiety and pain experiences. Family-centred care has the potential to promote families' holistic health, but its implementation is limited. Aim: To describe the barriers to family-centred care at a specific hospital in Gauteng. Setting: The study was contextual and was conducted at a specific hospital situated in Gauteng. Methods: A descriptive qualitative research design was used to collect data from 11 nurses and 14 primary caregivers of hospitalised children. Purposive sampling was used. Data were collected using semi-structured interviews and analysed using qualitative content analysis. Rigour through measures to enhance trustworthiness was ensured and ethical principles related to research with human participants were adhered to. Results: Three themes indicating the barriers to family-centred care emerged from the data, namely nurse-primary caregiver relationship, primary caregiver involvement, and ward structure and policy. Conclusion: Barriers to family-centred care involved interpersonal, environmental, and managerial dimensions of the hospital environment where children received care and treatment. A need to enhance family-centred care was therefore identified in order to address relational dimensions of the nurse-primary caregiver relationship, ward structure, and revision of current policies. Contribution: The article highlights barriers to family-centred care to enable action to be taken in the clinical environment to enhance a family-centred approach and improve the hospitalisation experience for children and caregivers.